Dental procedures in patients treated with antiplatelet or oral anticoagulation therapy - an anonymous survey - Ringel, Reingard; Maas, Renke (Gerodontology, 2015)
To investigate how German dentists adhere to recommendations regarding dental treatment of patients taking antiplatelet or oral anticoagulation therapy for cardiovascular protection.Discontinuation of antiplatelet or oral anticoagulation therapy prior to dental procedures is usually not recommended because the risk of thromboembolic events is higher than that of significant procedure-related bleeding.An anonymous questionnaire regarding the handling of and experiences with patients taking aspirin (acetylsalicylic acid) or vitamin-K-antagonists (phenprocoumon) was distributed to approximately 4500 dentists attending the national German Dentists Day 2011.Of 146 dentists who completed the questionnaire 77.4% and 27.6% stated that they perform tooth extractions under continued therapy with aspirin or vitamin-K-antagonists, respectively. When asked regarding the INR or Quick values, they require for tooth extractions in patients taking oral anticoagulants 29.5% of the dentists provided values that were outside the safe range (INR <=1.5 or >=3.5) and 90.7% accepted values too old to be clinically reliable. For pain relief after dental procedures, 71.2% of the dentists recommended ibuprofen notwithstanding the fact that it attenuates protective effects of aspirin and 10.2% would discontinue aspirin and prescribe ibuprofen or paracetamol (acetaminophen).Despite similar recommendations the majority of dentists perform tooth extractions in patients taking aspirin but not in patients taking vitamin-K-antagonists. Moreover, a potentially unfavourable drug interaction of aspirin and ibuprofen is frequently not considered. In patients taking vitamin-K-antagonists too many dentists rely on laboratory values that are too old or outside the recommended range.
EVALuna2:8696